Pengaruh Moralitas Individu, Budaya Organisasi, Good Corporate Governance Dan Ineffective Monitoring terhadap Kecendrungan Kecurangan Akuntansi pada LPD Se-Kecamatan Seririt - Nugroho, Bagus Yudianto; Dewi, Nyoman Ayu Wulan Trisna (Vokasi : Jurnal Riset Akuntansi, 2024)
This study aims to determine individual morality, organizational culture, good corporate governance and ineffective monitoring of the tendency of accounting fraud in LPDs in Seririt District. This research uses descriptive quantitative method. The study population was all LPDs in Seririt District, totaling 25 LPDs and with a total of 100 LPD administrators. In this study, the researcher used a sampling technique, namely purposive sampling. The sample used is 84 people. Data collection techniques by conducting observation and questionnaires. The data from this research instrument were collected and then tested for data quality by instrument testing (validity and reliability test), classical assumption test (normality test, multicollinearity test, and heteroscedasticity test), and hypothesis testing (multiple linear regression analysis, partial significance test (statistical test). t) and the coefficient of determination test). The results of this study indicate that individual morality, organizational culture, good corporate governance and ineffective monitoring partially have a positive and significant effect on the tendency of accounting fraud.